Conceptualizing digital finance as a precursor for financial inclusion and financial service usage in Uganda - Nickson Nagaaba; Rehema Batamuriza; James Basuta; Maryvian Owomugisha (Cogent Business & Management)
This study conceptualizes digital finance as mobile banking, mobile money, and agent banking in the context of Uganda, and quantifies their influence on the usage levels of financial services. Data were collected from 290 lead households from 15 districts of Uganda, benefiting from the Uganda Multi-Sectoral Food Security and Nutritional Project (UMFSNP). Confirmatory factor procedures confirmed the digital finance structure, and individual path coefficients were determined to explain their relationship with financial inclusion and usage of financial services. These results indicate that mobile money and agent banking are significantly associated with financial inclusion. The results indicate that only agent banking influences the usage of financial services. Mobile banking does not impact financial inclusion and the usage of financial services. This study implicates financial institutions, funding interventions, and the government of Uganda to embrace the appropriate financial services that are affordable to vulnerable people.